Cathedral at Durham
The compound piers, which belong to the larger rhythm of the major planning grid, take their form from their own superstructure- logically following the orders of the arches, the vaulting shafts, and the ribs of the aisle vault. The containment of thrust from aisle and nave vaults was no less logically solved by a system of transverse arches, hidden within the triforium stage, which took the load from the high vault and transferred it to external buttresses at the level of the aisle vault. These transverse arches are semicircular in form at the choir end of the building , but those in the nave are quadrant, and, although hidden, are truly flying buttresses.